AR smart poster for EEE - Kent, Lee Joon (Nanyang Technological University, 2020)
In this research, we explore the capabilities behind ARkit, an unparalleled augmented reality development kit from Apple. The feature sets were heavily scrutinized and compared, thus establishing several comparison criteria for different platforms. We also develop, debug and test applications, obtaining results that can assist in the efficient prototyping and progress for the AR applications that we are developing. We also dive deep into the world of content creation and video production. This work consists mainly of prototype research which tests the general performance, mapping of coordinates on different surface materials, how it reacts to complex textures and how it behaves under the influence of light, movement, and changes.